The Circulating Level of Noncoding RNA for Breast Cancer Diagnosis?A Meta-Analysis - Miao Wang; Guohui Li; Ranru Wei; Zhaojun Jia; Yao Gu; Aman Sattout; Jie Zhang; Feng Zhao (Re:GEN Open, 2021)
Background: The expression of noncoding RNAs (ncRNAs) is closely related to breast cancer progression. However, there is no systemic analysis of ncRNAs in breast cancer diagnosis of the blood circulatory system. Herein, we aimed to collect all the evidence to test the potential role of ncRNAs as novel biomarkers in human breast cancers.